Dendritic Structures Functionalized with Boron Clusters, in Particular Carboranes, and Their Biological Properties - Anne-Marie Caminade; Max Milewski; Evamarie Hey-Hawkins (MDPI AG, 2023)
The presence of a large number of boron atoms in boron clusters make them attractive tools for the treatment of cancer using boron neutron capture therapy (BNCT). Since the quantity of boron atoms present in the target cell directly affects the effectiveness of BNCT, the idea of gathering a high number of boron atoms in a single entity has emerged many years ago. In this perspective, using hyper-branched macromolecules such as dendrimers appears as an interesting solution. In this review, we will first present the synthesis of diverse dendritic entities (dendrimers, dendrons, and Janus dendrimers) that incorporate boron clusters, in particular carboranes, anywhere in their structure. Four parts of this review present the synthesis of dendrimers having boron clusters on the surface, or inside their structure, of dendrons and of Janus dendrimers, bearing boron clusters. Practically all these boronated dendritic structures were synthesized with the objective to study their biological properties, but in fact only a few of them have been tested against cancerous cells, and even a smaller number was tested in BNCT experiments. The biological experiments are discussed in the fifth part of this review. A good efficiency is generally observed with the boronated dendrimers, even in animal models, with an increase in their mean survival time (MST).